The Economics of the Network-Affilate Relationship: Comment - Graham, Daniel A.; Vernon, John M. (American Economic Review, 1975)
Comments on S. Besen and R. Soligo's article about the economics of the network-affiliate relationships in the television broadcasting industry in the U.S. Sale of advertising time on network programs; Supply curve of cleared time; Definition of the nondiscrinating monopsonist solution; Demand for network programming. (Из Ebsco)